Social Competency Analysis of Primary School Mobilizer Teachers - Aini, Luhur; Fitriana, Maulida Arum; Sumiadi, Raden (JUPE : Jurnal Pendidikan Mandala, 2023)
The purpose of this study is to determine the form of social competence of mobilizing teachers. This qualitative research uses a phenomenological approach with a descriptive method. Data collection techniques in this study are observation, interview, and documentation techniques. Interview. This research has several stages, namely data reduction, data presentation and conclusions. Test the validity of the data in this study, researchers used observational persistence and triangulation. The results of this study show that the competence of mobilizing teachers in cluster 1 Sukadana, with good social competence in understanding teacher interaction with students, teacher interaction with school principal, teacher interaction with colleagues, teacher interaction with parents and teacher interaction with the community. The mobilizing teacher communicates with students to take creative actions, applies social-emotional materials, the mobilizing teacher establishes good communication with students, the mobilizing teacher applies humanist values to students, the mobilizing teacher always maintains communication with the principal, the mobilizing teacher actively assists the principal for the progress of the school, the mobilizing teacher is always compact with colleagues in every activity,  The mobilizing teacher always helps colleagues, the mobilizing teacher always maintains good communication with the parents of students, the mobilizing teacher involves the parents of students in school activities, the mobilizing teacher keeps in touch with the parents of the students, the mobilizing teacher is involved in activities in the community, mobilizing teachers to become role models for the community, this is carried out in fostering the social spirit of students, especially in cluster 1 Sukadana.